Impact of cavity on interatomic Coulombic decay - Lorenz S. Cederbaum (Nature Portfolio, 2021)
Interatomic Coulombic decay, ICD, is commonly observed in systems weakly bound to different environments. Here the authors discuss the ICD in an electromagnetic cavity and show that the entanglement of atoms can change ICD rates substantially and be used to control the ICD process.